ON LEARNING LOGIC IN 17th CENTURY TRANSYLVANIA - DREHE, Iovan (Studia Universitatis Babeș-Bolyai Philosophia, 2022)
The purpose of this paper is to provide a glimpse on the method and content of teaching logic/dialectic in the Principality of Transylvania in the 17th century from the perspective of Miklós Bethlen with references to two important local scholars: Pál Keresztúri and Janos Apáczai Csere, who is better known as being the first Hungarian encyclopaedist. In addition to this, the paper will contain for comparison a short survey of what Jan Amos Komenský had to say about teaching logic.